Adsorbent as well as preparation method and application thereof
By modifying the molecular sieve from molybdenum, zirconium and purterium sources, and depositing naphthylsilane on the surface, combined with alumina modification, an efficient adsorbent was prepared, which solved the problem of poor adsorption of VOCs and achieved efficient adsorption of pollutants in VOCs, wastewater and air.
Patent Information
- Application Number
- CN202411928007.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
AI Technical Summary
The existing adsorbents have poor adsorption effect on volatile organic matter (VOC), which limits their application areas.
Molybdenum sources, zirconium sources and purtergent sources are used to modify the molecular sieve, and naphthylsilane is deposited on its surface, and further modified with alumina is prepared to prepare an efficient adsorbent.
It significantly improves the adsorption effect of adsorbents and has excellent adsorption properties for VOC, ammonia nitrogen in wastewater and formaldehyde in air. It is suitable for VOC treatment and wastewater treatment and other fields.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorbents, and in particular to an adsorbent and a preparation method and application thereof. Background Art
[0002] In recent years, the volatile organic compound (VOC) emissions from the industrial solvent use industry account for more than 20% of the total anthropogenic emissions in the country. VOC is an important precursor to the formation of ozone and secondary organic aerosols, which not only causes environmental pollution, but also threatens people's health. In the solvent use industry, representative enterprises mainly include furniture, coatings and ink manufacturing, automobiles, electronics and other industries. These industries are characterized by being dominated by small and medium-sized enterprises, with a large number and covering a wide range. Their VOC emissions are mainly low concentration and large air volume. Among VOC control technologies, the adsorption method has the advantages of economy and applicability, and the core of the adsorption method is the selection of adsorbents. Existing adsorbents also have the problem of poor adsorption effect on VOCs, which limits the application field of adsorbents. Summary of the invention
[0003] The present invention provides an adsorbent and a preparation method and application thereof, which solve the problem of poor adsorption effect of the adsorbent in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a method for preparing an adsorbent, comprising the following steps: S1, after mixing the acid solution and aluminum powder, adding the modified molecular sieve and continuing to mix to obtain a mixed solution; S2, after adding a viscosity enhancer and a volume expander into the mixed solution, the mixed solution is formed into an oil-ammonia column, washed, dried, and calcined to obtain an adsorbent; The preparation method of the modified molecular sieve comprises the following steps: The molybdenum source, the zirconium source, the lutetium source, the solvent and the molecular sieve are mixed, dried and calcined to obtain the modified molecular sieve.
[0005] As a further technical solution, in step S2, the washing is performed using secondary water at 25-35°C.
[0006] As a further technical solution, the mass ratio of the modified molecular sieve to the aluminum powder is 0.8~1.2:1.
[0007] As a further technical solution, in step S1, the acid solution is an aqueous nitric acid solution, and the mass ratio of nitric acid to water in the aqueous nitric acid solution is 1:13-15; the mass ratio of the acid solution to the aluminum powder is 3.2-4.2:1.
[0008] As a further technical solution, in step S2, the viscosity enhancer includes one or two of starch and methyl cellulose; the volume expander includes one or more of ethanol, ethylene glycol, propylene glycol, isobutanol, and isopentanol; and the molecular sieve is one of Y-type molecular sieve, ZSM-5 molecular sieve, MOR-type molecular sieve, β-type molecular sieve, SAPO-34 molecular sieve, and MFI-type molecular sieve.
[0009] As a further technical solution, the preparation method of the modified molecular sieve comprises the following steps: The molybdenum source, zirconium source, lutetium source, solvent and molecular sieve are mixed, dried, calcined and mixed with naphthylsilane to carry out vapor deposition reaction, and the solid phase product is washed and dried to obtain the modified molecular sieve.
[0010] In the present invention, after the molecular sieve is modified by a molybdenum source, a zirconium source and a lutetium source, naphthylsilane is deposited on the surface thereof, thereby further improving the adsorption effect of the adsorbent.
[0011] As a further technical solution, the mass ratio of the molybdenum source, the zirconium source and the lutetium source is 2-3:7:1; The mass ratio of the zirconium source to the molecular sieve is 1:2-3; The mass ratio of the zirconium source to the solvent is 1:2.
[0012] In the present invention, the molecular sieve is modified by using a molybdenum source, a zirconium source and a lutetium source in a mass ratio of 2 to 3:7:1, thereby further improving the adsorption effect of the adsorbent.
[0013] As a further technical solution, the molybdenum source includes ammonium molybdate; the zirconium source includes one or more of zirconium nitrate, zirconium carbonate, and zirconium sulfate; and the lutetium source includes one or both of lutetium nitrate and lutetium acetate.
[0014] As a further technical solution, the mass ratio of naphthylsilane to molecular sieve is 1-2:4; The naphthyl silane includes one or more of 1-naphthyl trimethoxy silane, 1-naphthyl triethoxy silane, and 1-naphthyl phenyl silane.
[0015] As a further technical solution, the vapor deposition reaction time is 7 to 10 hours.
[0016] The present invention also proposes the use of the adsorbent prepared by the preparation method in adsorbing VOC.
[0017] The invention also proposes the application of the adsorbent prepared by the preparation method in wastewater treatment.
[0018] In the present invention, wastewater treatment may be, for example, printing and dyeing wastewater treatment, petrochemical wastewater treatment, etc.
[0019] In the present invention, the adsorption of VOCs may be, for example, the adsorption of VOCs in the air, the adsorption of VOCs in industrial emissions, and the like.
[0020] The working principle and beneficial effects of the present invention are: In the present invention, when preparing the adsorbent, the molecular sieve is first modified by using a molybdenum source, a zirconium source and a lutetium source, and then modified by using alumina, which significantly improves the adsorption effect of the adsorbent. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In the following examples and comparative examples, secondary water is water with an electrical conductivity of less than 10 us / cm.
[0023] Example 1 A method for preparing an adsorbent comprises the following steps: S1, add 40g concentrated nitric acid to 150g deionized water, stir for 5min, form nitric acid solution recorded as A, add the prepared nitric acid solution A to 2000g deionized water, and mark it as nitric acid aqueous solution; after mixing the nitric acid aqueous solution and aluminum powder for 30min, add the modified molecular sieve at a uniform speed and continue mixing to obtain a mixed solution, the mass ratio of the modified molecular sieve to the aluminum powder is 0.8:1, and the mass ratio of the nitric acid aqueous solution to the aluminum powder is 4.2:1; S2, after adding starch and ethanol to the mixed solution, forming it through an oil-ammonia column, washing it with secondary water at 30°C at a flow rate of 500 mL / min for 30 min, drying it at 60°C for 8 h, and calcining it at 600°C for 5 h to obtain an adsorbent; The preparation method of the modified molecular sieve comprises the following steps: ammonium molybdate, zirconium nitrate, lutetium acetate, water, and ZSM-5 molecular sieve are mixed, dried, and calcined to obtain a modified molecular sieve; The mass ratio of ammonium molybdate, zirconium nitrate and lutetium acetate is 1:7:1, the mass ratio of zirconium nitrate and ZSM-5 molecular sieve is 1:3, and the mass ratio of zirconium nitrate and water is 1:2.
[0024] Example 2 A method for preparing an adsorbent comprises the following steps: S1, add 30g concentrated nitric acid to 150g deionized water, stir for 5min, form nitric acid solution recorded as A, add the prepared nitric acid solution A to 2000g deionized water, and mark it as nitric acid aqueous solution; after mixing the nitric acid aqueous solution and aluminum powder for 30min, add the modified molecular sieve at a uniform speed and continue mixing to obtain a mixed solution, the mass ratio of the modified molecular sieve to the aluminum powder is 1.2:1, and the mass ratio of the nitric acid aqueous solution to the aluminum powder is 3.2:1; S2, after adding starch and ethanol to the mixed solution, forming it through an oil-ammonia column, washing it with secondary water at 35°C at a flow rate of 500 mL / min for 30 min, drying it at 60°C for 8 h, and calcining it at 600°C for 5 h to obtain an adsorbent; The preparation method of the modified molecular sieve comprises the following steps: ammonium molybdate, zirconium nitrate, lutetium acetate, water, and ZSM-5 molecular sieve are mixed, dried, and calcined to obtain a modified molecular sieve; The mass ratio of ammonium molybdate, zirconium nitrate and lutetium acetate is 1:7:1, the mass ratio of zirconium nitrate and ZSM-5 molecular sieve is 1:2, and the mass ratio of zirconium nitrate and water is 1:2.
[0025] Example 3 A method for preparing an adsorbent comprises the following steps: S1, add 60g concentrated nitric acid to 150g deionized water, stir for 5min, form nitric acid solution recorded as A, add the prepared nitric acid solution A to 2000g deionized water, mark as nitric acid aqueous solution; after mixing the nitric acid aqueous solution and aluminum powder for 30min, add the modified molecular sieve at a uniform rate and continue mixing to obtain a mixed solution, the mass ratio of the modified molecular sieve to the aluminum powder is 0.8:1, and the mass ratio of the nitric acid aqueous solution to the aluminum powder is 4:1; S2, after adding starch and ethanol to the mixed solution, forming it through an oil-ammonia column, washing it with secondary water at 25°C at a flow rate of 500 mL / min for 30 min, drying it at 60°C for 8 h, and calcining it at 600°C for 5 h to obtain an adsorbent; The preparation method of the modified molecular sieve comprises the following steps: ammonium molybdate, zirconium nitrate, lutetium acetate, water, and ZSM-5 molecular sieve are mixed, dried, and calcined to obtain a modified molecular sieve; The mass ratio of ammonium molybdate, zirconium nitrate and lutetium acetate is 1:7:1, the mass ratio of zirconium nitrate and ZSM-5 molecular sieve is 1:2, and the mass ratio of zirconium nitrate and water is 1:2.
[0026] Example 4 The only difference between this embodiment and embodiment 3 is that the mass ratio of ammonium molybdate, zirconium nitrate and lutetium acetate is 4:7:1.
[0027] Example 5 The only difference between this embodiment and embodiment 3 is that the mass ratio of ammonium molybdate, zirconium nitrate and lutetium acetate is 2:7:1.
[0028] Example 6 The only difference between this embodiment and embodiment 3 is that the mass ratio of ammonium molybdate, zirconium nitrate and lutetium acetate is 3:7:1.
[0029] Example 7 The only difference between this embodiment and embodiment 6 is that the preparation method of the modified molecular sieve comprises the following steps: Ammonium molybdate, zirconium nitrate, lutetium acetate, water, and ZSM-5 molecular sieve are mixed, dried, calcined, and then mixed with 3-aminopropyltriethoxysilane, and vapor deposition reaction is carried out for 7 hours. The solid phase product is washed and dried to obtain a modified molecular sieve; the mass ratio of 3-aminopropyltriethoxysilane to ZSM-5 molecular sieve is 1:2.
[0030] Example 8 The only difference between this embodiment and embodiment 6 is that the preparation method of the modified molecular sieve comprises the following steps: Ammonium molybdate, zirconium nitrate, lutetium acetate, water, and ZSM-5 molecular sieve are mixed, dried, calcined, and then mixed with 1-naphthylphenylsilane, and vapor deposition reaction is carried out for 7 hours. The solid phase product is washed and dried to obtain a modified molecular sieve; the mass ratio of 1-naphthylphenylsilane to ZSM-5 molecular sieve is 1:2.
[0031] Example 9 The only difference between this embodiment and embodiment 6 is that the preparation method of the modified molecular sieve comprises the following steps: Ammonium molybdate, zirconium nitrate, lutetium acetate, water, and ZSM-5 molecular sieve are mixed, dried, calcined, and then mixed with 1-naphthyltrimethoxysilane, and a vapor deposition reaction is carried out for 10 hours. The solid phase product is washed and dried to obtain a modified molecular sieve; the mass ratio of 1-naphthyltrimethoxysilane to ZSM-5 molecular sieve is 1:4.
[0032] Comparative Example 1 The difference between this comparative example and Example 3 is only that no ammonium molybdate is added.
[0033] Comparative Example 2 The only difference between this comparative example and Example 3 is that no zirconium nitrate is added.
[0034] Comparative Example 3 The difference between this comparative example and Example 3 is only that lutetium acetate is not added.
[0035] Bulk density: The bulk density of the adsorbents prepared in Examples 1 to 3 is 0.64 g / mL; Average strength: the average strength of the adsorbent prepared in Example 1 is 48N, the average strength of the adsorbent prepared in Example 2 is 45N, and the average strength of the adsorbent prepared in Example 3 is 50N; The average particle size of the adsorbents prepared in Examples 1 to 3 was 1.8 mm, the roundness was above 0.95, the fluidity was good, the surface of the sphere was relatively smooth, without cracks, and there was no breakage after immersion in 15 wt% hydrochloric acid for 48 hours. The specific surface area was 280 to 320 m 2 / g, the pore volume is 0.5~0.6mL / g, and the average pore diameter is 7~11nm.
[0036] Application Example 1 The adsorbents prepared in Examples 1 to 9 and Comparative Examples 1 to 3 were used to adsorb the flue gas of VOC gas. The flue gas temperature was 30°C, and the flue gas flowed through a purification chamber containing the adsorbent at a flow rate of 1 m / s. The concentrations of toluene and ethyl acetate were detected by a toluene detector and an ethyl acetate detector, respectively, and the removal rate was calculated. The removal rate = [(concentration before treatment - concentration after treatment) / concentration before treatment] × 100%. The results are shown in Table 1.
[0037] Table 1 Test results
[0038] Compared with Comparative Examples 1 to 3, the toluene removal rate and ethyl acetate removal rate of the adsorbents prepared in Examples 1 to 9 are higher, indicating that when preparing the adsorbent, the molecular sieve is first modified with a molybdenum source, a zirconium source, and a lutetium source, and then modified with alumina, which significantly improves the adsorption effect of the adsorbent.
[0039] Compared with Examples 3 to 4, the toluene removal rate and ethyl acetate removal rate of the adsorbent prepared in Examples 5 to 6 are higher, indicating that the adsorption effect of the adsorbent is further improved after the molecular sieve is modified by using a molybdenum source, a zirconium source, and a lutetium source in a mass ratio of 2 to 3:7:1.
[0040] Compared with Examples 6 and 7, the toluene removal rate and ethyl acetate removal rate of the adsorbent prepared in Examples 8 and 9 are higher, indicating that after the molecular sieve is modified with a molybdenum source, a zirconium source, and a lutetium source, naphthylsilane is deposited on its surface, which further improves the adsorption effect of the adsorbent.
[0041] Application Example 2 The adsorbents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to decolorization tests respectively, and the steps were as follows: The printing and dyeing wastewater was treated by ozone catalytic oxidation method: the adsorbent was filled in a 100mm×100mm×100mm cubic reaction container, and the printing and dyeing wastewater (flow rate 50mL / min) and ozone (flow rate 35mg / L) were introduced. The hydraulic retention time of the printing and dyeing wastewater in the container was maintained for 25 minutes. The chromaticity and CODcr of the inlet and outlet printing and dyeing wastewater were measured, and the decolorization rate and CODcr removal rate were calculated. The results are shown in Table 2.
[0042] Table 2 Test results
[0043] Compared with comparative examples 1 to 3, the adsorbents prepared in Examples 1 to 3 have higher decolorization rate and CODcr removal rate for printing and dyeing wastewater, indicating that the adsorbent prepared in the present invention can be applied to the field of wastewater treatment and has excellent effects on wastewater decolorization and CODcr removal.
[0044] The adsorbents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were respectively subjected to ammonia nitrogen adsorption test, and the steps were as follows: 1 g of adsorbent was added to 100 mL of ammonia nitrogen wastewater with an ammonia nitrogen concentration of 0.1 g / L, stirred and mixed, centrifuged, and the upper clear liquid was taken to determine the ammonia nitrogen concentration in the clear liquid and calculate the ammonia nitrogen adsorption amount. The results are shown in Table 3.
[0045] Table 3 Test results
[0046] Compared with comparative examples 1 to 3, the adsorbents prepared in embodiments 1 to 3 have a higher adsorption capacity for ammonia nitrogen in ammonia nitrogen wastewater, indicating that the adsorbent prepared in the present invention can also be applied to the field of wastewater treatment and has an excellent adsorption effect on ammonia nitrogen in wastewater.
[0047] Application Example 3 The adsorbents prepared in Examples 1 to 3 were respectively tested for removal rate of VOC (formaldehyde) in the air according to the standard QB / T2761-2006 "Method for Determining the Purification Effect of Indoor Air Purification Products". During the test, the initial formaldehyde concentration in the experimental cabin was 1.4-2.0 mg / m 3 When the formaldehyde concentration in the experimental chamber increases to the maximum value and stabilizes for 1 minute, start the fan and start timing. Record the formaldehyde concentration in the chamber every 5 minutes. The test duration is set to 15 minutes. Repeat the test 4 times for each adsorbent, take the average value of the test results, and record the removal rate. The results are shown in Table 4 below.
[0048] Table 4 Test results
[0049] The adsorbents prepared in Examples 1 to 3 have a removal rate of (formaldehyde) in the air of more than 89%, indicating that the adsorbents prepared in the present invention can also be used in the field of air purification and have excellent adsorption effects on VOC (formaldehyde) in the air.
[0050] Application Example 4 They were added into conical flasks containing 50 mL of petrochemical wastewater, placed in a constant temperature oscillator and oscillated at 298.15 K for 24 hours, and then the supernatant was taken and the COD value of the wastewater after adsorption was determined using the method of HJ 828-2017 "Determination of Chemical Oxygen Demand of Water Quality - Dichromate Method". The results are shown in Table 5 below.
[0051] Table 5 Test results
[0052] After the adsorbents prepared in Examples 1 to 3 adsorbed petrochemical wastewater, the COD value dropped to below 15 mg / L (10.5 to 11.6 mg / L), meeting the discharge requirements for wastewater COD in GB 31571-2015, indicating that the adsorbent prepared in the present invention can also be used in the field of petrochemical wastewater treatment, and has an excellent effect on purifying petrochemical wastewater and reducing the COD value in water.
[0053] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an adsorbent, characterized in that: The following steps are involved: S1, after mixing the acid solution and aluminum powder, adding the modified molecular sieve and continuing to mix to obtain a mixed solution; S2, after adding a viscosity enhancer and a volume expander into the mixed solution, the mixed solution is formed into an oil-ammonia column, washed, dried, and calcined to obtain an adsorbent; The preparation method of the modified molecular sieve comprises the following steps: The molybdenum source, the zirconium source, the lutetium source, the solvent and the molecular sieve are mixed, dried and calcined to obtain the modified molecular sieve.
2. The method for preparing an adsorbent according to claim 1, characterized in that: The mass ratio of the modified molecular sieve to the aluminum powder is 0.8-1.2:
1.
3. The method for preparing an adsorbent according to claim 1, characterized in that: In step S1, the acid solution is a nitric acid aqueous solution, and the mass ratio of nitric acid to water in the nitric acid aqueous solution is 1:13-15; the mass ratio of the acid solution to the aluminum powder is 3.2-4.2:
1.
4. The method for preparing an adsorbent according to claim 1, characterized in that: In step S2, the viscosity enhancer includes one or two of starch and methyl cellulose; the volume expander includes one or more of ethanol, ethylene glycol, glycerol, isobutanol, and isopentanol; and the molecular sieve is one of Y-type molecular sieve, ZSM-5 molecular sieve, MOR-type molecular sieve, β-type molecular sieve, SAPO-34 molecular sieve, and MFI-type molecular sieve.
5. The method for preparing an adsorbent according to claim 1, characterized in that: The preparation method of the modified molecular sieve comprises the following steps: The molybdenum source, zirconium source, lutetium source, solvent and molecular sieve are mixed, dried, calcined and mixed with naphthylsilane to carry out vapor deposition reaction, and the solid phase product is washed and dried to obtain the modified molecular sieve.
6. The method for preparing an adsorbent according to claim 1 or claim 5, characterized in that: The mass ratio of the molybdenum source, the zirconium source and the lutetium source is 2-3:7:1; The mass ratio of the zirconium source to the molecular sieve is 1:2-3.
7. The method for preparing an adsorbent according to claim 1 or claim 5, characterized in that: The molybdenum source includes ammonium molybdate; the zirconium source includes one or more of zirconium nitrate, zirconium carbonate, and zirconium sulfate; and the lutetium source includes one or both of lutetium nitrate and lutetium acetate.
8. The method for preparing an adsorbent according to claim 5, characterized in that: The mass ratio of naphthylsilane to molecular sieve is 1-2:4; The naphthyl silane includes one or more of 1-naphthyl trimethoxy silane, 1-naphthyl triethoxy silane, and 1-naphthyl phenyl silane.
9. The method for preparing an adsorbent according to claim 5, characterized in that: The vapor deposition reaction time is 7 to 10 hours.
10. Use of the adsorbent prepared according to the preparation method according to any one of claims 1 to 9 in adsorbing VOC or in treating wastewater.